IRON REMOVAL OF GROUNDWATER ON THE TOWER-COLUMN WITH FOAM FILTER - and (Municipal economy of cities. Series: «Economy science», 2013)
Shows the construction process parameters and performance bashtkolon with foam filter for iron removal of water.